2014
DOI: 10.3126/bibechana.v12i0.11670
|View full text |Cite
|
Sign up to set email alerts
|

Study the effect of sodium nitrite as a green corrosion inhibitor for the sputter-deposited tungsten-based ternary alloys in 0.5 M NaCl solution

Abstract: Effects of sodium nitrite on the corrosion resistance and mechanism of the sputter-deposited W-80Cr-10Zr and W-42Cr-5Ni alloys were studied using corrosion tests and open circuit potential (OCP) measurements in 0.5 M NaCl solution, open to air at 25ºC. The corrosion resistance property of the W-80Cr-10Zr and W-42Cr-5Ni alloys was enhanced by the use of environmental friendly corrosion inhibitor of sodium nitrite. Higher corrosion resistance property and passivation behavior was observed for the W-42Cr-5Ni allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Three sputter-deposited W-xCr alloys were characterized as nano-crystalline structure having an apparent grain size between 8 and 15 nm [31] from XRD patterns using Scherrer formula as describes elsewhere [54,80]. Before the immersion tests and AR-XPS analyses, the alloy specimens were mechanically polished with a SiC paper having the grit number 1500 in cyclohexane, degreased by acetone, and dried by blowing dry air to remove the oxide film formed on the surface of the alloys as described elsewhere [81][82][83]. The average corrosion rate was estimated using weight loss methods as described elsewhere [84,85].…”
Section: Preparation and Characterization Of W-xcr Alloysmentioning
confidence: 99%
“…Three sputter-deposited W-xCr alloys were characterized as nano-crystalline structure having an apparent grain size between 8 and 15 nm [31] from XRD patterns using Scherrer formula as describes elsewhere [54,80]. Before the immersion tests and AR-XPS analyses, the alloy specimens were mechanically polished with a SiC paper having the grit number 1500 in cyclohexane, degreased by acetone, and dried by blowing dry air to remove the oxide film formed on the surface of the alloys as described elsewhere [81][82][83]. The average corrosion rate was estimated using weight loss methods as described elsewhere [84,85].…”
Section: Preparation and Characterization Of W-xcr Alloysmentioning
confidence: 99%
“…Past researches had reported that some organic [20][21][22][23][24][25] and inorganic [26][27][28][29][30] compounds were used as eco-friendly corrosion inhibitors because they form complexes with metal ions on metal/alloy surface. Investigations of corrosion-inhibiting ability of inorganic radicals or ions, e.g., nitrites, molybdates, tungstates, polyphosphates are now being increasingly used as eco-friendly inhibitor due to their zero-toxic nature [10,[31][32][33][34][35][36]. It was reported that calcium nitrate acted as retarder against chloride-induced concrete structures like well-known corrosion inhibitor of calcium nitrite [37] because it is also cheaper, less harmful and more available [38].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, adsorption of these phytoconstituents on the surfaces of the corroded Al and Cu enhances to fabrication of highly stable and less reactive layers, which blocks anodic/cathodic or both sides, and hence prevents significantly the corrosion rates of the metals in the presence of the inhibitors [63]. The degree of such corrosion-preventing layer is mostly in proportionate to the inhibitor concentrations, and it affects the physicochemical characteristics as described above in the adsorption models [64].…”
Section: Cooked-oil Residue (Cor)mentioning
confidence: 99%